Consensus-based perspectives of pediatric inpatient eating disorder services - O'Brien, A.; Mccormack, J.; Hoiles, K.; Watson, H.; Anderson, Rebecca; Hay, P.; Egan, Sarah (John Wiley & Sons, Inc., 2018)
© 2018 Wiley Periodicals, Inc. Objective: There are few evidence-based guidelines for inpatient pediatric eating disorders. The aim was to gain perspectives from those providing and receiving inpatient pediatric eating disorder care on the essential components treatment. Method: A modified Delphi technique was used to develop consensus-based opinions. Participants (N=74) were recruited for three panels: clinicians (n=24), carers (n=31), and patients (n=19), who endorsed three rounds of statements online. Results: A total of 167 statements were rated, 79 were accepted and reached a consensus level of at least 75% across all panels, and 87 were rejected. All agreed that families should be involved in treatment, and thatpsychological therapy be offered in specialist inpatient units. Areas of disagreement included that patients expressed a desire for autonomy in sessions being available without carers, and that weight gain should be gradual and admissions longer, in contrast to carers and clinicians. Carers endorsed that legal frameworks should be used to retain patients if required, and that inpatients are supervised at all times, in contrast to patients and clinicians. Clinicians endorsed that food access should be restricted outside meal times, in contrast to patients and carers. Discussion: The findings indicate areas of consensus in admission criteria, and that families should be involved in treatment, family involvement in treatment, while there was disagreement across groups on topics including weight goals and nutrition management. Perspectives from patients, carers, and clinicians may be useful to consider during future revisions of best practice guidelines.